Amygdalar Stimulation Produces Alterations on Firing Properties of Hippocampal Place Cells - Kim, Eun Joo; Kim, Earnest S.; Park, Mijeong; Cho, Jeiwon; Kim, Jeansok J. (SOC NEUROSCIENCE, 2012)
Stress is a biologically ubiquitous factor that, when perceived uncontrollable by humans and animals, can have lingering adverse effects on brain and cognitive functions. We have previously reported that rats that experienced inescapable-unpredictable stress subsequently exhibited decreased stability of firing rates of place cells in the CA1 hippocampus, accompanied by impairments in CA1 long-term synaptic potentiation and spatial memory consolidation. Because the elevated level of glucocorticoid hormones and the heightened amygdalar activity have been implicated in the emergence of stress effects on the hippocampus, we investigated whether administration of corticosterone and electrical stimulation of the amygdala can produce stress-like alterations on hippocampal place cells. To do so, male Long-Evans rats chronically implanted with tetrodes in the hippocampus and stimulating electrodes in the amygdala were placed on a novel arena to forage for randomly dispersed food pellets while CA1 place cells were monitored across two recording sessions. Between sessions, animals received either corticosterone injection or amygdalar stimulation. We found that amygdalar stimulation reliably evoked distress behaviors and subsequently reduced the pixel-by-pixel correlation of place maps across sessions, while corticosterone administration did not. Also, the firing rates of place cells between preamygdalar and postamygdalar stimulation recording sessions were pronouncedly different, whereas those between precorticosterone and postcorticosterone injection recording sessions were not. These results suggest that the heightened amygdalar activity, but not the elevated level of corticosterone per se, reduces the stability of spatial representation in the hippocampus by altering the firing rates of place cells in a manner similar to behavioral stress.
Keywords: LONG-TERM POTENTIATION; ELECTRICAL-STIMULATION; SYNAPTIC PLASTICITY; LATERAL AMYGDALA; CARDIOVASCULAR-RESPONSES; PLASMA-CORTICOSTERONE; CORTICAL AFFERENTS; INDUCED IMPAIRMENT; PYRAMIDAL NEURONS; UNIT-ACTIVITY